2006
DOI: 10.1037/0096-1523.32.4.944
|View full text |Cite
|
Sign up to set email alerts
|

Representation and execution of vocal motor programs for expert singing of tonal melodies.

Abstract: Three experiments were conducted to study motor programs used by expert singers to produce short tonal melodies. Each experiment involved a response-priming procedure in which singers prepared to sing a primary melody but on 50% of trials had to switch and sing a different (secondary) melody instead. In Experiment 1, secondary melodies in the same key as the primary melody were easier to produce than secondary melodies in a different key. Experiment 2 showed that it was the initial note rather than key per se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Thus, the role of practice trials in the current study was in their influence on subsequent trials, within and across domains. Various priming paradigms have pointed to the role of persistence in speech and music production (Bock, 1986; Jungers, Palmer, & Speer, 2002; Zurbriggen, Fontenot, & Meyer, 2006). For instance, Jungers et al (2002) found that tempos can carry over from one produced keyboard melody to the next.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the role of practice trials in the current study was in their influence on subsequent trials, within and across domains. Various priming paradigms have pointed to the role of persistence in speech and music production (Bock, 1986; Jungers, Palmer, & Speer, 2002; Zurbriggen, Fontenot, & Meyer, 2006). For instance, Jungers et al (2002) found that tempos can carry over from one produced keyboard melody to the next.…”
Section: Discussionmentioning
confidence: 99%
“…Note that there is a rich literature regarding acoustical features of professional singing (for reviews, see Sundberg, 1987, 1999). However, in only a few isolated studies has pitch production in professional singers been examined (Vurma and Ross, 2006; Zurbriggen et al, 2006). These studies revealed that when professional singers are asked to produce pitch intervals, they can be out of tune by 20–25 cents, with respect to the equally tempered scale.…”
Section: Introductionmentioning
confidence: 99%
“…This error is typically not noticed by expert listeners (Vurma and Ross, 2006). In addition, features like the accuracy of the first note of the melody and melodic contour play a role in motor planning, as shown by asking singers to prepare for producing a melody (Zurbriggen et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…The intensity of the singer’s formant, the presence of vibrato, the maximum phonational frequency range, and loudness increase with musical experience (e.g., Brown, Rothman, & Sapienza, 2000; Hunter, Svec, & Titze, 2006; Mendes, Rothman, Sapienza, & Brown, 2003). Yet, just a few isolated studies have focused on the mechanisms underlying accurate pitch production in professional singers (Vurma & Ross, 2006; Zurbriggen, Fontenot, & Meyer, 2006). Zurbriggen and collaborators (2006) asked expert singers to prepare to sing a melody, which was produced in 50% of the cases but, in the remaining 50% of the cases, the singers were asked to switch to another melody.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, just a few isolated studies have focused on the mechanisms underlying accurate pitch production in professional singers (Vurma & Ross, 2006; Zurbriggen, Fontenot, & Meyer, 2006). Zurbriggen and collaborators (2006) asked expert singers to prepare to sing a melody, which was produced in 50% of the cases but, in the remaining 50% of the cases, the singers were asked to switch to another melody. The accuracy of the first note of the melody and the melodic contour were affected in the different melody, thus suggesting that these elements are relevant in motor planning.…”
Section: Introductionmentioning
confidence: 99%